Dehydroleucodine, a Sesquiterpene Lactone from Gynoxys verrucosa, Demonstrates Cytotoxic Activity against Human Leukemia Cells - Ordóñez Vivanco, P. (2016)
The sesquiterpene lactones dehydroleucodine (1) and leucodine (2) were isolated from Gynoxys verrucosa, a species used in traditional medicine in southern Ecuador. The activity of these compounds was determined against eight acute myeloid leukemia (AML) cell lines and compared with their activity against normal peripheral blood mononuclear cells. Compound 1 showed cytotoxic activity against the tested cell lines, with LD50 values between 5.0 and 18.9 ?M. Compound 2 was inactive against all of the tested cell lines, demonstrating that the exocyclic methylene in the lactone ring is required for cytotoxic activity. Importantly, compound 1 induced less toxicity to normal blood cells than to AML cell lines and was active against human AML cell samples from five patients, with an average LD50 of 9.4 ?M. Mechanistic assays suggest that compound 1 has a similar mechanism of action to parthenolide (3). Although these compounds have significant structural differences, their lipophilic surface signatures show striking similarities.